U-Shaped Tube Based Liquid–Solid Triboelectric Nanogenerator for Harvesting Unutilized Compressed Air Energy - Xuhang Cai; Zhijian Liu; Jingming Dong; Haoji Li; Jiamu Han; Jiaming Huang; Haotian Chen (Micromachines, 2023)
Due to a lack of technologies that harvest green and sustainable energy, unutilized compressed air energy during the operation of pneumatic systems is wasted. Liquid–solid triboelectric nano-generators (L-S TENGs) have been widely used as an advanced technology with broad development prospects due to their advantages of a simple structure and long service life. Among them, liquid–solid triboelectric nanogenerators with tube structures have great potential for coupling multiple physical effects and integrating them into a single device. Herein, a U-shaped tube triboelectric nanogenerator composed of fluorinated ethylene propylene (FEP) and copper foil (UFC-TENG) is proposed to directly harvest unutilized compressed air energy. The UFC-TENG can collect unutilized compressed air energy with a stable peak voltage and current of approximately 33 V and 0.25 μA, respectively. When the alternating frequency of the liquid is 0.9 Hz, the unutilized compressed air can drive the UFC-TENG unit with an inner diameter of 12 mm, achieving a maximum output power of 3.93 μW at an external load resistance of 90 MΩ. The UFC-TENG is a novel driving method for L-S TENGs and demonstrates the promising potential of TENGs in the harvesting of unutilized compressed air energy in pneumatic systems.